2016
DOI: 10.1021/acs.est.6b01159
|View full text |Cite
|
Sign up to set email alerts
|

Breath Biomarkers to Measure Uptake of Volatile Organic Compounds by Bicyclists

Abstract: Breath biomarkers were used to study uptake of traffic-related volatile organic compounds (VOCs) from urban bicycling. Breath analysis was selected because it is one of the least invasive methods to assess urban traveler exposure. Research hurdles that were overcome included considering that factors other than on-road exposure can influence concentrations in the body, and absorbed doses during a trip can be small compared to baseline body burdens. Pre-trip, on-road, and post-trip breath concentrations and ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The longer duration of the cycling trip also increased the inhaled doses. Recent Bigazzi's studies [17,18] aimed to determine (i) biomarkers that could be used to assess a cyclist's uptake of pollutants in urban environment, and (ii) optimal cycling speeds to minimize a cyclist's inhalation of those biomarkers. The work in [17] aimed to determine a way to assess the inhalation of harmful pollutants by cyclists for trips through different kinds of areas.…”
Section: Cycling and Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer duration of the cycling trip also increased the inhaled doses. Recent Bigazzi's studies [17,18] aimed to determine (i) biomarkers that could be used to assess a cyclist's uptake of pollutants in urban environment, and (ii) optimal cycling speeds to minimize a cyclist's inhalation of those biomarkers. The work in [17] aimed to determine a way to assess the inhalation of harmful pollutants by cyclists for trips through different kinds of areas.…”
Section: Cycling and Air Pollutionmentioning
confidence: 99%
“…Recent Bigazzi's studies [17,18] aimed to determine (i) biomarkers that could be used to assess a cyclist's uptake of pollutants in urban environment, and (ii) optimal cycling speeds to minimize a cyclist's inhalation of those biomarkers. The work in [17] aimed to determine a way to assess the inhalation of harmful pollutants by cyclists for trips through different kinds of areas. The study identified 26 volatile organic compounds (VOCs) such as CFCs, benzene, styrene and carbon disulfide, and compared the amounts of these compounds that were present in ambient air with the amounts that were present in a cyclist's breath after cycling through a given area.…”
Section: Cycling and Air Pollutionmentioning
confidence: 99%
“…Analytes of interest were chosen according to the literature review of VOCs determination in ambient air in different cities [28][29][30][31][32][33] and previous studies of compounds detected in the exhausts of six arbitrarily chosen cars of different models and production years [27]. Chosen analytes belong to several classes of pollutants having various physicochemical properties (Table S1 in Supplementary Materials).…”
Section: Chemicalsmentioning
confidence: 99%
“…(2)(3)(4) VOCs are a concern because they give rise to the generation of photochemical oxidants and suspended particulate matter that damage humans and plants. (5) Also, VOCs have been reported to cause health problems such as carcinogenesis after longterm exposure; thus, countermeasures are required. (6)(7)(8)(9)(10)(11)(12) If we can constantly monitor the types and concentrations of VOCs used in manufacturing processes and laboratories, we can maintain a safe work environment.…”
Section: Introductionmentioning
confidence: 99%